(untitled) (Medico Legal Update, 2021)
Background: The overuse of chemical pesticides without proper Personal Protective Equipment (PPE) use has put vegetable farmers at risk and has been an extreme concern over the past decades in the Maldives. Therefore, this study aimed to describe the patterns of chemical pesticide use and determinants of PPE use to diminish chemical exposure. Method: This cross-sectional study applied a two-stage random sampling method to select the study subjects to respond a structured questionnaire. The multiple logistic regression was applied to determine the association. Results: Of 306 respondents, 90% used chemical pesticides while only 23% used PEE. Themultivariable analysis indicated the use of PPE was significantly associated with education attainment (adj.OR=3.17, 95% CI=1.80-5.57, p-value=<0.001), amount of chemical pesticide used per month (adj.OR=2.20, 95% CI=1.37-4.43, p-value=0.002), main sources of pesticide information (adj.OR=2.31, 95% CI=1.33- 4.01, p-value=0.003), hired someone to spray chemical pesticides (adj. OR=2.46, 95% CI=1.13-4.31, p-value=0.02), and ever participated in any farming-related trainings (adj.OR=2.97, 95% CI=1.63-5.49, p-value=<0.001). Conclusions: Almost all of the farmers used chemical pesticides and less than a quarter used full PPE. Educational attainment, quantity of pesticides used, sources of pesticide information and other farming practices have a strong relationship with PPE use.